Literasi Digital: Revitalisasi Inovasi Teknologi - Ahmad Rohman; Masduki Asbari; Dimas Rezza (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to encourage people to always have the latest information and be ready to adapt to technological developments. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to oral narratives from the BukaTalks Bukalapak Youtube channel entitled